2018
DOI: 10.1002/2017wr022259
|View full text |Cite
|
Sign up to set email alerts
|

Improved Characterization of Groundwater Flow in Heterogeneous Aquifers Using Granular Polyacrylamide (PAM) Gel as Temporary Grout

Abstract: The range of options for investigation of hydraulic behavior of aquifers from boreholes has been limited to rigid, cumbersome packers, and inflatable sleeves. Here we show how a new temporary borehole sealing technique using soft grains of polyacrylamide (PAM) gel as a sealing material can be used to investigate natural groundwater flow dynamics and discuss other possible applications of the technology. If no compressive stress is applied, the gel packing, with a permeability similar to open gravel, suppresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Poorly consolidated rock or unstable boreholes could make the installation and removal of liners difficult. This would require other ways to seal the borehole such as permanently grouting the cable in place or perhaps the polyacrylamide gel beads described by Klepikova et al (2018). Also, while the early issues of small amounts of flow along the cable behind the liner described by Maldaner et al (2019) have been resolved by increasing the hydrostatic pressure in the liner, this may be difficult at sites with shallow water tables.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poorly consolidated rock or unstable boreholes could make the installation and removal of liners difficult. This would require other ways to seal the borehole such as permanently grouting the cable in place or perhaps the polyacrylamide gel beads described by Klepikova et al (2018). Also, while the early issues of small amounts of flow along the cable behind the liner described by Maldaner et al (2019) have been resolved by increasing the hydrostatic pressure in the liner, this may be difficult at sites with shallow water tables.…”
Section: Resultsmentioning
confidence: 99%
“…While this can help, the majority of the borehole remains unsealed, and therefore, vertical flow within the borehole is still possible and has in some cases led to inflated flow measurements in point dilution experiments (Maldaner et al, 2018). Less conventional methods have been tested recently to prevent free convection and flow within borehole such as the use of granular polyacrylamide gel beads (Klepikova et al, 2018). Finally, flexible, impermeable fabric borehole liners have been demonstrated as an effective means to temporarily seal boreholes.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have reported the existence of another key factor in the heat transfer, which is free convection caused by density differences arising from vertical temperature gradients (Diment 1967;Gretener 1967;Pfister and Rybach 1995;Berthold and Börner 2008;Eppelbaum and Kutasov 2011;Klepikova et al 2018). The critical parameters for the free convection process can be indicated by the following equation (Diment and Urban 1983):…”
Section: Shut-in Conditionmentioning
confidence: 99%
“…Thereby, they can fill tight, small cracks and pores and induce fundamental changes in permeability reduction due to their strong impact on pore plugs. Furthermore, there are a wide variety of factors that exert a considerable influence on controlling nanoparticles migration, such as increasing flow velocity and rise of pressure drop during the low-salinity water-flooding procedures [19]. In this paper, a mathematical model of polymer-nanoparticles-assisted injectivity performance was developed to control the mobility of nanoparticles migration.…”
Section: Introductionmentioning
confidence: 99%
“…PAM (polyacrylamide): Due to its high value of molecular weight (approximately more than 10 6 gr./mole) that usually performed as a thickening agent for the aqueous solutions. Moreover, PAM has its stable properties at the temperature of 90 °C at the normal salinity and at the salinity of seawater; the temperature is set up at 62 °C Hence, it is worthwhile that this type of polymer would be restricted on the on-shore performances [ 19 ].…”
Section: Introductionmentioning
confidence: 99%